Sosialiasi Pendidikan, Program Indonesian Pinntar (PIP) Dan KIP-Kuliah Didesa Wringintelu Kecamatan Puger Kabupaten Jember Tahun 2023 - Mustofa , Mustofa; Aditya Nugraha , Raafi; Sulastri , Sulastri; Abdul Gufron, Shehona (JURNAL PENGABDIAN MASYARAKAT (JPM), 2023)
Education is very important for human life, because with education we get knowledge and experience in every process. He also said, "Whoever wants goodness in the hereafter, then with knowledge. Whoever wants both then with knowledge.» From the opinion of the hadith above, it shows that education is one of the main assets to achieve many things. The method used in this service is socialization which is packaged in the form of lectures, presentation of material and notifications of assistance provided by the government for each education. During the event, we, as the organizing committee, instructed the public to bring their KTP and KK for data collection on children who did not receive PIP and KIP-College in their institutions. Based on the data collection conducted, there were 140 children who registered for the PIP program, including 59 children from SDN 01 Wringintelu, 26 children from SDN 02 Wringintelu, 31 children from SDN 03 Wringintelu, and 24 children from SMP Puger. With the existence of scholarships in the form of PIP and KIP-College issued by the government it can reduce the occurrence of children dropping out of school, both due to economic factors, and so on.